Meditasi Mindfulness Untuk Mereduksi Perilaku Impulsif - Meri Meri; Partono Nyanasuryanadi; Suherman Suherman; Ary Sugata; Satya Adhinugroho (Journal of Constitutional, Law and Human Rights, 2025)
This review article examines the effectiveness of mindfulness meditation in reducing impulsive behaviors. Impulsivity is a significant psychological trait associated with various mental health disorders, including ADHD, and emotional dysregulation. Over recent years, mindfulness meditation has gained popularity as a therapeutic intervention for addressing impulsivity due to its potential to enhance self-awareness, and emotional regulation. This article synthesizes findings from empirical studies that explore the impact of mindfulness practices on impulsive behaviors. The review also considers the underlying mechanisms through which mindfulness meditation may exert its influence, such as attentional control, executive functioning, and emotional resilience. Additionally, the article evaluates the methodological quality of the studies included, results, and potential areas for future research. The findings suggest that mindfulness meditation can be an effective strategy for reducing impulsive behavior, offering valuable insights for clinicians, researchers, and individuals seeking non-pharmacological interventions.